If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + 3 = 12 Reorder the terms: 3 + h = 12 Solving 3 + h = 12 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + h = 12 + -3 Combine like terms: 3 + -3 = 0 0 + h = 12 + -3 h = 12 + -3 Combine like terms: 12 + -3 = 9 h = 9 Simplifying h = 9
| 1.7*100+x=825 | | -2(f+3)=3(5-3f) | | -8s+13=-7s-12 | | 35+5x-11=-6(-x)+8x | | X^4-7x^2=0 | | 4x+4=21 | | 3y+8-y=y+4 | | 4k^2-2k-5=0 | | 3x+19=7x-11 | | 4x-5(x-2)=9c-14 | | 4(n-8)+5(-6-2n)=-68 | | 4(n-8)+5(-6-2n)=-69 | | 3x+7=5x-x+0 | | 29=a+7 | | v=15x^3+52x^2+32x | | -12t-28=9t+47-(-4t) | | 3v+4=19 | | x^2+20x+42=0 | | 2x+72=12-3x | | 0.8+0.25x=0 | | 9(x-6)=6-30 | | 4q+-24=12 | | x+9f+10=5j | | 15(3x+1)-243(5x-2)=0 | | 25/x+6=5/6 | | 1n-1=18 | | -9x+7y=2 | | -19w+-20=18 | | c-2y=24 | | -13x+6=-12-9 | | x-2-(3+(7-2x))=-6 | | 0.625x(a-2)=10 |